Pariwisata, Masyarakat dan Kebudayaan: Studi Antropologi Pariwisata Pantai Marina di Pajukukang Bantaeng, Sulawesi Selatan - Satria Wulandari; Rifal; Ahmadin; Abdul Rahman; Muh. Zainuddin Badollahi (Politeknik Pariwisata Makassar, Indonesia, 2020)
This article discusses the development of tourism with an anthropological approach to tourism in the Marina Pajujukang Bantaeng Beach, South Sulawesi. The results of this study indicate that: (1) Government efforts in developing marina beach tourism are trying to improve the human resources of the village of Baruga by conducting socialization and trying to complete facilities incomplete such as clean water filter (2) Community involvement in tourism development by supporting government programs for the advancement of marina beach tourism objects and participating directly in the development of Marina beach such as being a builder at the beginning of Marina beach construction until the Marina beach is like being security officer, janitor and waitress at a hotel in the Marina beach area. (3) The impacts felt by the community in developing the Marina beach are two, namely in the economic field for example increasing community income, opening new jobs and opening business opportunities for the Baruga village community while in the socio-cultural field there are two impacts namely positive and negative impacts. An example of the positive impact is the increasing public insight about tourist culture through the temporary negative impact that is starting to affect the local community on the culture of tourists who come to visit the Marina beach. This research is a qualitative descriptive study. Data collection techniques used were observation, interviews, and documentation. The data obtained is then processed using data analysis techniques such as data reduction, data presentation and conclusion making. And also the data validation using Member Check. From the results of research that has been found it seems that every development of tourism needs to be involved by all groups, especially the community, not just prioritizing investors. Because the essence of the success of the trip tour if the surrounding community enjoys economic results.